The impact of institutional volatility on financial volatility in transition economies: a GARCH family approach - Christopher A. Hartwell (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
The volatility of financial markets has been a relevant topic for transition economies, as the countries of Central and Eastern Europe and the former Soviet Union have seemingly en-dured high levels of volatility in their financial sectors during the transition process. But what have been the determinants of this financial volatility? This paper posits that institutional changes, and in particular the volatility of various crucial institutions, have been the major causes of financial volatility in transition. Examining 20 transition economies over various time-frames within the period 1993-2012, this paper applies the GARCH family of models to examine financial volatility as a function of institutional volatility. The results from the EGARCH and TGARCH modelling supports the thesis that more advanced and more stable institutions help to dampen financial sector volatility at their levels, while institutional volatility feeds through directly to financial sector volatility in transition.
URN:NBN:fi:bof-201408072077
Keywords: G20; O43; P30; 330; institutions; financial sector; volatility; transition; GARCH; EGARCH; TGARCH